ANTIBACTERIAL ACTIVITY TEST OF KETAPANG LEAF ETHANOL EXTRACT (Terminalia catappa L,) AND GARLIC TUBER (Allium sativum L,) AGAINST Pseudomonas aeruginosa ATCC 27853 - Ivan Julianus Mesak (Universitas STRADA Indonesia, 2022)
Pseudomonas aeruginosaare bacteria that are widely distributed in nature. These bacteria cause several infectious diseases, namely dermatitis, otitis externa, folliculitis, eye infections, and infections of burns, as well as of the respiratory tract. Clinical treatment so far is long term and carries the risk of developing bacterial resistance to antibiotics. The purpose of this study was to determine the ability of the antibacterial activity of the ethanol extract of ketapang leaves (Terminalia catappa L.) garlic (Allium sativum L.),The purpose of this study was to determine the single dose and combination of ethanol extract of ketapang leaves (Terminalia catappa L.) and garlic (Allium sativum L.) which have effective bacterial activity againstPseudomonas aeruginosa ATCC 27853 and the values of the Minimum Inhibitory Concentration (MIC) and Minimum Killing Concentration from the ethanol extract of ketapang leaves (Terminalia catappa L.) and garlic (Allium sativum L.). Alilicin compound in garlic, the tannin and flavonoid compounds in the ketapang plant act as antibacterial compounds. This research is an experimental research using diffusion and dilution methods. Garlic extract and ketapang leaf extract were obtained by maceration method extraction using 96% ethanol solvent for 5 days. The extract concentrations obtained were 100%, 50%, 25%, 12.5%, 6.25%, 3.125%, 1.563%, 0.781%, 0.391%, 0.196%. The data obtained were then analyzed based on bacterial growth Pseudomonas aeruginosa ATCC 27853 was tested in a test tube and selectively mediated by the dilution method by determining the Minimum Inhibitory Concentration (MIC) based on observations in the test tube where the smallest concentration of the test material in the tube showed that the culture results were starting to become clear (no bacterial growth) and the Minimum Kill Concentration. ). Was determined based on the results of observations of the test material and the smallest concentration of the test material on PSA media which was indicated by the absence of colony growth on solid media. The test results showed that the ethanol extract of Ketapang leaves (Terminalia catappa L.) and garlic bulbs (Allium sativum L.) singleand the combination of both have antibacterial activity against Pseudomonas aeruginosa ATCC 2785. The combination of ethanol extract of ketapang leaves and garlic bulbs at a concentration of 50%:50% was the most effective extract as an antibacterial against Pseudomonas aeruginosa ATCC 27853, Minimum Kill Concentration (KBM) ethanol extract of ketapang leaves and garlic bulbs against Pseudomonas aeruginosa ATCC 27853 is 50%.